FROM AUTHORIAL DRAWINGS TO THE PARAMETRIC MODELING OF TERRITORIAL OCCUPATION: REPRESENTATION AND MODELING INFLUENCES IN THE PROCESS OF DESIGNING THE URBAN SPACE - Moura, Ana Clara Mourão; Santana, Sheyla Aguilar (Revista Brasileira de Cartografia, 2014)
The objective of this article is to argue that we are living in a new era in the drawing process of urban planning and urban management, and this change is the result of developments in the technologies of spatial representation. The era of post-modernism is being replaced by a new moment dictated by parameterization. What preceded this new condition was the significant evolution of geo-technologies, the wide dissemination of their resources and the facilitation of their usage due to the availability of data and applications on the worldwide network of computers. The laws have encouraged the access to information and defined that the urban projects, necessarily of collective interest, should be discussed and agreed with the participation of the community, which has brought as a requirement to issue the visualization of the information. To lead the discussion on the relationship between urban design and its graphical expression and mapping, it’s presented a brief overview of urban history until today, to defend a proposal of a periodization in the history of urban representation, through its relationship with methodologies of urban planning. The text presents as conclusion the indication of contemporary values, which are: interoperability between systems, investment in visualization technology, integration of the community in volunteered mapping and, above all, methodological processes based on Parametric Modeling of Territory Occupation.